Resistivity and PTC behaviour of electro-conductive PVOH/MWNT and EVOH/MWNT nanocomposites. (15th March 2016) - Kim, K. R.; Park, E-S.
Abstract : Electro-conductive poly(vinyl alcohol)/multi-walled carbon nanotube (PVOH/MWNT) and poly(ethylene- co -vinyl alcohol) (EVOH)/MWNT nanocomposites were prepared by precipitation saponification method. The MWNT was functionalised by electron beam irradiation in air at 1200 kGy doses. The electrical resistivity, thermal and mechanical properties, and positive temperature coefficient (PTC) behaviour of these nanocomposites were investigated. The melting and crystallisation peak temperatures of both nanocomposite systems were shifted at a higher temperature with the increase in saponification time. Their crystallinity and mechanical strength also increased with saponification time, indicating an increase in intermolecular hydrogen bond between vinyl alcohol groups. With the saponification time, PTC peak temperature of EVA28/MWNT and EVA40/MWNT nanocomposites was shifted at a higher temperature and followed by a negative temperature coefficient (NTC) of resistivity. However, the saponified PVAc/MWNT nanocomposites showed only NTC behaviour over a temperature range of 30–140°C.